Giant Ferroelectric Polarization in Ultrathin Ferroelectrics via Boundary-Condition Engineering - Xie, Lin (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.